2020
DOI: 10.1001/jamanetworkopen.2020.27082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Social Norm Email Feedback Program on the Unnecessary Prescription of Nimodipine in Ambulatory Care of Older Adults

Abstract: Key Points Question Can a social norm–based behavioral intervention delivered by email reduce non–evidence-based prescriptions of nimodipine for treating cognitive impairment in older adults? Findings This randomized clinical trial included 1811 high–nimodipine-prescribing physicians within the national health care system for older adults in Argentina. Physicians randomized to the social norm email treatment group reduced nimodipine prescribing after receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(59 reference statements)
0
6
0
3
Order By: Relevance
“…Physicians in the intervention group made fewer inappropriate prescriptions than physicians in the control group, mean 93.25 prescriptions (95% CI: 89.27–97.24) versus 98.99 (95% CI: 95.00–102.98). 341 In Thailand, a large study of 11 915 patients across four community hospitals found that computerized decision support systems that detect potentially inappropriate medications were associated with 13.3 percentage points decrease (from 87.7% to 74.4%) in potentially inappropriate medications. 275 …”
Section: Resultsmentioning
confidence: 99%
“…Physicians in the intervention group made fewer inappropriate prescriptions than physicians in the control group, mean 93.25 prescriptions (95% CI: 89.27–97.24) versus 98.99 (95% CI: 95.00–102.98). 341 In Thailand, a large study of 11 915 patients across four community hospitals found that computerized decision support systems that detect potentially inappropriate medications were associated with 13.3 percentage points decrease (from 87.7% to 74.4%) in potentially inappropriate medications. 275 …”
Section: Resultsmentioning
confidence: 99%
“…They can also increase the demand for vaccination (Batteux et al, 2022;Busso et al, 2015;Dombkowski et al, 2017;Martinez Villarreal, 2023;Milkman et al, 2022;Moehring et al, 2023). Messages that employ digital tools are proven to benefit meaningful public health decisions and reduce the cost of these interventions, and they can even change the behavior of doctors and nurses (Cuesta et al, 2021;Kannisto et al, 2014;Murtaugh et al, 2005;Torrente et al, 2020). The results presented in this paper constitute evidence that information interventions are also effective in promoting telemedicine use.…”
Section: Introductionmentioning
confidence: 73%
“…Feedback and comparison of clinical practices is a strategy that can be used to improve compliance with a desired change in clinical behaviour [ 31 , 32 ]. Clinical performance feedback has been shown to be an effective low-cost intervention in several settings for changing prescribing behaviour [ 17 , 33 , 34 ]. Although systematic reviews have concluded that audit and feedback overall may provide only a small benefit, a review looking at various mailed intervention techniques reported that well-constructed mailed interventions, focusing on a single topic, and providing patient data, have the potential to evoke significant changes in physician prescribing [ 35 ].…”
Section: Discussionmentioning
confidence: 99%